Przywiązanie, parentyfikacja i trauma relacyjna a status tożsamości w okresie wyłaniającej się dorosłości - Róg-Mazurek, Jakub (Kultura-Społeczeństwo-Edukacja, 2021)
Nowadays, it is young adults, not adolescents, who face the challenge of determining their own identity. This process, compared to previous generations, takes place in qualitatively different conditions. Moreover, the current attributes of an adult have become obsolete. For this reason, making the vision of oneself reality may be associated with various difficulties. The root of the failure to clarify identity is to be found in the original bond with the guardian and in all experiences that disrupt attachment. Among these types of experiences, relational trauma and parentification are worth mentioning. Relational trauma can be said to be when a child experiences repeated neglect in the context of a close relationship. A similar phenomenon is parentification. The aim of the research is to check 1) whether there are significant differences between the identified identity statuses and 2) whether the variables (attachment style, experience of parentification and relational trauma) differentiate the identity status in the period of emergingadulthood. Three identity statuses are distinguished: Identity of anxiety type (N = 23), identity of diffuse type (N = 30) and identity of type achieved (N = 43). Each type differs in terms of both the experiences and the severity of the identity dimensions.